2022
DOI: 10.1002/inf2.12302
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐robust stretchable electrode for e‐skin: In situ assembly using a nanofiber scaffold and liquid metal to mimic water‐to‐net interaction

Abstract: The development of stretchable electronics will thrive on the novel interface structure to solve the stretchability-conductivity dilemma, which is still a great challenge. Herein, we report a nano-liquid metal (LM)-based high-robust stretchable electrode (NHSE) with a self-adaptable interface that mimics water-tonet interaction. Based on in situ assembly of electrospun elastic nano bers scaffold and electrosprayed LM nanoparticles, the NHSE exhibits an extremely low sheet resistance of 52 mΩ/□. It is not only … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…It is observed that the resistance increases by 1.14, 3.41, and 7.95% under the strain of 100, 200, and 300%, respectively. In addition, Figure E shows LMs/SHL-LIG/Ecoflex has the lowest sheet resistance of 3.54 mΩ per square and second highest stretchability up to 480% compared with those of previously reported stretchable conductors. ,, After 7000 stretching cycles under the strain of 300%, the resistance of LMs/SHL-LIG/Ecoflex shows excellent stability to quickly return back to its initial value after each stretching cycle (insets), as shown in Figure F. The very small resistance variation of ∼8% after each stretching cycle makes it the best among other existing stretchable conductors ,, (Figure S3).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…It is observed that the resistance increases by 1.14, 3.41, and 7.95% under the strain of 100, 200, and 300%, respectively. In addition, Figure E shows LMs/SHL-LIG/Ecoflex has the lowest sheet resistance of 3.54 mΩ per square and second highest stretchability up to 480% compared with those of previously reported stretchable conductors. ,, After 7000 stretching cycles under the strain of 300%, the resistance of LMs/SHL-LIG/Ecoflex shows excellent stability to quickly return back to its initial value after each stretching cycle (insets), as shown in Figure F. The very small resistance variation of ∼8% after each stretching cycle makes it the best among other existing stretchable conductors ,, (Figure S3).…”
Section: Resultsmentioning
confidence: 56%
“…The excellent stretchability of Ecoflex enables the demonstration of a uniaxial tensile strain of ∼480% for the as-prepared LMs/SHL-LIG/Ecoflex sample with a size of 5 × 8 mm 2 (Figure B). Robustness and stability in the electrical resistance are important criteria for the performance of stretchable conductors. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, fiber substrates have attracted attention due to their unique properties, and flexible electronic devices based on LM and fiber materials have also been widely reported . Further, our research and some other groups have shown that stretchable circuits with super-stretchability, high conductivity, stability, breathability, and safety can be obtained by printing LM on electrospun substrates. However, these studies have mainly focused on the fabrication of stretchable electrodes, which do not possess the ability to directly fix rigid ICs. Therefore, it is of great value and significance to introduce rigid ICs into LM circuits (LMC) while maintaining device stretchability and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed triboelectric nanogenerator has provided ideas for the fabrication of self-powered wearable sensors [ 24 , 25 ]; moreover, selecting an appropriate detection position significantly improves the sensing signal strength. In addition, the wearability of sensors is also important for continuous wearable monitoring, which requires these sensors to be flexible and have low biotoxicity, and the dielectric layer material is the key for flexible stretchable sensors [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%